Comparative study of papanicolaou smear and colposcopy in the evaluation of cervical lesions - Mohan, Priyanka; M., Lakshmidevi; Venkatesh, Shreedhar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Cervical cancer is the third most common type of cancer among females. Study aims to critically evaluate the sensitivity and specificity of colposcopy versus papanicolaou (Pap) smear in the early detection of dysplasias. Its secondary objective to correlate the findings in the evaluation of unhealthy cervix by cytology, colposcopy and colposcopy guided biopsy. Methods: This was a tertiary care teaching hospital based, prospective, cross sectional study done in Department of Obstetrics and Gynaecology, at Vydehi Institute of Medical Sciences and Research Centre, Bangalore, conducted on 200 women attending Gynaecology OPD. Results: PAP smear was taken for all 200 patients. 73% of smear was found to be normal, 11% showed inflammatory atypia, 9% showed low grade squamous intraepithelial lesion (LSIL), 3.5% showed atypical squamous cells of undetermined significance (ASCUS) and 3.5% showed High Grade Squamous Intraepithelial Lesion (HSIL). Among the 200 cases studied, 38% (76/200) were diagnosed as colposcopically abnormal. Among the abnormal cases, AW areas were diagnosed in 4%. Punctate pattern of vessels was seen in 5% of women. Normal findings was present in 62%, Erosion cervix in 6%, inflammatory changes were seen in 6% and polyps were diagnosed in 7.5%, leucoplakia was found in 2% and unsatisfactory colposcopy finding was seen in 4% and underwent endocervical curettage. 32 cases out of 200 women were positive on Pap smear. 66 out of 200 women were positive on Biopsy. Pap smear was positive in 22 out of 66 biopsy proven positive cases. Conclusions: The commonest presenting complaint was vaginal discharge (182/200; 91% of the patients. the PAP smear is found to have sensitivity of 33.33% and specificity of 92.54%. colposcopy is found to have sensitivity of 81.82% and specificity of 82.84%.